Polyurethane composite material embedded with liquid repair network and preparation method of polyurethane composite material

By embedded liquid repair network in polyurethane materials, the synergy between liquid repair agents and micro-nano carriers is used to solve the problem of low repair efficiency of self-repair materials in the prior art under large-scale damage, and achieve rapid and efficient repair and improvement of multiple repair capabilities.

CN119823562AActive Publication Date: 2025-04-15WUHAN RES INST OF MATERIALS PROTECTION

Patent Information

Application Number
CN202510069661.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-15
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

The existing self-repair polyurethane materials have low repair efficiency and long repair time under large-scale injuries, and their performance is unstable under multiple injuries and complex environmental conditions.

Method used

By embedded a liquid repair network in the polyurethane matrix, fast and efficient repair is achieved by utilizing the high flowability of the liquid repair agent and the controlled release characteristics of the micro-nano carrier.

Benefits of technology

It significantly improves the ability to repair multiple times and environmental adaptability, shortens the repair time, and improves the performance stability of the material in complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823562A_ABST
    Figure CN119823562A_ABST
Patent Text Reader

Abstract

The invention discloses a polyurethane composite material embedded with a liquid repair network and a preparation method thereof, and belongs to the technical field of high polymer materials, the polyurethane composite material comprises 40-60 parts of a polyurethane prepolymer, 5-20 parts of repair agent carrier particles, 10-30 parts of a liquid repair agent and 0.1-1 part of a dispersant. The composite material provided by the invention solves the problems that a polyurethane material is easy to damage and low in repair efficiency in long-term use. The composite material disclosed by the invention has rapid, efficient and self-adaptive repairing performance under large-scale damage and multiple damage, is suitable for complex environments such as acid-base and high temperature, and has important application prospects in the fields of various industrial equipment, flexible electronic equipment, automobiles, buildings and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a polyurethane composite material with an embedded liquid repair network and a preparation method thereof. Background Art

[0002] In modern industry, polyurethane materials are widely used in many fields such as automobiles, aerospace, construction, and electronic equipment due to their excellent mechanical properties, wear resistance, weather resistance, and good processability. These advantages make polyurethane materials an important component of many high-performance products. However, during long-term use, they will inevitably be affected by the external environment, especially under high load, high temperature or harsh climate conditions, the materials are prone to cracks, fatigue or aging. These damages not only affect the service life of the material, but may also cause equipment failure or structural failure, thereby affecting the safety and reliability of the product. Therefore, how to improve the damage resistance of polyurethane materials and extend their service life has become an important research direction in the field of materials science.

[0003] With the continuous development of technology, self-healing materials have gradually become one of the hot spots in the research of high-performance materials. Self-healing materials can automatically restore their structure and function after encountering external damage, avoiding the cumbersome process of traditional repair methods and having high application potential, especially in aerospace, automobile, construction and electronic equipment. Existing self-healing polyurethane materials mainly rely on mechanisms such as dynamic covalent bonds or hydrogen bonds to achieve self-healing. However, in the case of large-area cracks or multiple damages, the repair efficiency and material integrity are significantly reduced, mainly due to limited molecular migration and exhaustion of repair resources. In addition, the performance of such materials in complex chemical environments and extreme temperatures often cannot meet actual needs.

[0004] The invention patent of the prior art CN 110305466 A proposes a polyurethane / epoxy resin blend with shape memory, self-repair and recyclable functions and its preparation method. The polyurethane / epoxy resin blend is a homogeneous blend of polyurethane and epoxy resin or a two-phase phase-separated blend formed by cross-linking and curing with a curing agent after the two are blended. Among them, the polyurethane is a linear polyurethane material containing a disulfide bond on the main chain, the epoxy resin is a cyclohydrogen resin prepolymer containing a furan ring on the side group, and the curing agent contains a maleimide group. The preparation method of the polyurethane / epoxy resin homogeneous blend is: dissolve the polyurethane and the epoxy resin prepolymer in an organic solvent, stir and blend at a temperature of 60 to 80°C, stir evenly, and dry at a temperature of 60 to 80°C to obtain. This invention improves the shape memory, self-repair and recycling characteristics of the polyurethane material through a blending method, enhances the mechanical properties of the polyurethane at room temperature, and does not affect the recyclability of the polyurethane at high temperatures. However, it does not solve the problems of multiple damage repair, rapid response and performance stability in complex environments, and is not suitable for promotion and application. The prior art invention patent CN 111499833 A introduces polythiol containing disulfide self-repairing functional groups into polyurethane to obtain a self-repairing polyurethane resin. Although the anti-corrosion performance is taken into account, the distribution and release mechanism of the repair agent are relatively simple, and the technology does not fully consider the multiple repair capabilities and long-term environmental adaptability, and is not suitable for promotion and application.

[0005] Therefore, it is a technical problem that technicians in this field urgently need to solve to provide a polyurethane composite material with an embedded liquid repair network that can achieve rapid and efficient repair under large-scale damage and improve multiple repair capabilities and environmental adaptability. Summary of the invention

[0006] In view of this, the present invention embeds a liquid repair network in the polyurethane matrix and utilizes the high fluidity of the liquid repair agent and the controlled release characteristics of the micro-nano carrier. It can not only achieve rapid and efficient repair under large-scale damage, but also significantly improve the multiple repair capabilities and environmental adaptability, providing a new technical solution for the practical application of self-healing materials.

[0007] To achieve the above object, the present invention adopts the following technical solution:

[0008] A polyurethane composite material with an embedded liquid repair network comprises the following raw materials in parts by weight:

[0009] 40-60 parts of polyurethane prepolymer, 5-20 parts of repair agent carrier particles, 10-30 parts of liquid repair agent and 0.1-1 part of dispersant;

[0010] The polyurethane prepolymer is prepared by mixing isocyanate and polyol in a molar ratio of 1.8-2.2:1 under the catalysis of a catalyst; and the amount of the catalyst is 0.5-2 parts;

[0011] The liquid repair agent is prepared by mixing epoxy resin and mercaptan in a mass ratio of 1-4:1, and is used for a cross-linking reaction at the crack.

[0012] Furthermore, the isocyanate is 4,4'-diphenylmethane diisocyanate (MDI), and the polyol is polyether polyol or polyester polyol.

[0013] Furthermore, the repair agent carrier particles are modified SiO2 microspheres, the surface of which is treated with a silane coupling agent to improve the bonding strength with the polyurethane matrix, and the particle size of the microspheres is 10-100 nm.

[0014] In the present invention, the microsphere particle size is controlled within the range of 10-100nm because the SiO2 microspheres in this range are at nanoscale, which can improve the strength, toughness and impact resistance of the polyurethane matrix. A particle size less than 10nm may cause microsphere agglomeration, reduce dispersibility and enhancement effect; and a particle size greater than 100nm will weaken the interface effect of nano-enhancement, reduce the uniformity and performance of the material. Simultaneously, the epoxy resin and the mercaptan are controlled at a mass ratio of 1-4:1 because the epoxy groups in the epoxy resin molecules provide crosslinking points, and their ratio directly determines the rigidity and structural stability of the repair network, and the mercaptan (-SH) in the mercaptan reacts rapidly with the epoxy groups to form flexible segments, which increases the ductility of the repair network. When the mass ratio is close to 1:1, the number of mercaptan groups is close to the metering requirements of the epoxy groups, forming a crosslinked network with a higher density, which is suitable for enhancing the strength after repair. When the mass ratio is 4:1, the mercaptan groups are slightly excessive, the proportion of flexible segments is increased, and the repair material has better toughness and fatigue resistance, and is adapted to large strain environments. When the content of epoxy resin increases, the viscosity of the repair agent increases, which may reduce its permeability in the cracks. The proportion of thiol can be appropriately increased according to the actual application to effectively reduce the viscosity and improve the fluidity and filling of the repair agent in microcracks.

[0015] Furthermore, the catalyst is diphenylphosphonic acid, which can accelerate the cross-linking reaction between epoxy groups and thiol groups in the liquid repair agent and improve the repair efficiency; the dispersant is polyether-modified siloxane, which is used to improve the dispersibility of the repair agent carrier particles in the prepolymer.

[0016] Furthermore, the present invention further comprises 0.5-5 parts of additives for enhancing weather resistance or mechanical properties.

[0017] Furthermore, the additive is a mixture of any one or more of an antioxidant, an ultraviolet absorber and a flame retardant.

[0018] Furthermore, the antioxidant is 2,6-di-tert-butyl-p-cresol, the ultraviolet absorber is benzophenone, and the flame retardant is decabromophenylethylene.

[0019] The additives of the present invention can enhance the weather resistance, UV resistance and flame retardancy of the composite material. These additives are selected according to actual application requirements, and can improve the stability of the material while meeting the requirements of long-term use in different environments.

[0020] The present invention also provides a method for preparing the polyurethane composite material with an embedded liquid repair network, comprising the following steps:

[0021] (1) Injection and encapsulation of liquid repair agent: Heat the epoxy resin at 50-60°C to a viscous state; slowly add the thiol under continuous stirring to ensure uniform mixing; continue stirring for 10-15 minutes until a uniform and transparent liquid repair agent is formed;

[0022] (2) Weighing each raw material according to the above weight proportions, mixing the liquid repair agent with the repair agent carrier particles; treating the mixture of the repair agent and the carrier under vacuum conditions for 10-20 minutes to ensure that the liquid repair agent penetrates into the pores of the carrier; rapidly freezing the carrier injected with the liquid repair agent at -40°C; and performing vacuum freeze drying using a freeze drying device to remove excess solvent to ensure stable storage of the repair agent;

[0023] (3) Preparation of polyurethane prepolymer: preparing a polyurethane prepolymer with controllable viscosity by reacting isocyanate with polyol under the action of a catalyst;

[0024] (4) Forming of the composite material: The carrier particles of the encapsulated repair agent are ultrasonically uniformly dispersed in the polyurethane prepolymer, and then formed by molding, pouring or spraying, and cured at 50-80°C for 2-6 hours to obtain a polyurethane composite material with an embedded liquid repair network.

[0025] Furthermore, the preparation method of the repair agent carrier particles is: disperse SiO2 microspheres in anhydrous ethanol to ensure that the particles are fully suspended, add 0.1-5% of silane coupling agent, and stir evenly; reflux at 60°C for 2-4h to form a chemical bond between the silane coupling agent and the SiO2 surface; wash with ethanol for multiple times to remove unreacted silane coupling agent, and finally dry at 80°C to obtain modified SiO2 microspheres.

[0026] Furthermore, the silane coupling agent is γ-aminopropyltriethoxysilane or γ-methacryloxypropyltrimethoxysilane.

[0027] Furthermore, in step (2), the vacuum pressure is 10 Pa, the freeze-drying temperature is -60°C, and the freeze-drying time is 12-24 hours.

[0028] Furthermore, the composite material prepared by the present invention can achieve self-repair in an acid-base environment (pH of 2-12) and high temperature (within 200°C).

[0029] The present invention solves the problems of low repair efficiency and long repair time under large-scale damage in the prior art through the synergistic effect of liquid repair agents and micro-nano carriers. The high fluidity of the liquid repair agent and the controllable release mechanism of the micro-nano carrier enable the material to respond quickly and achieve efficient repair when damage occurs. The repair agent is stored and released by the micro-nano carrier, so it can quickly penetrate and fill cracks when cracks occur, and then quickly solidify through the cross-linking reaction of epoxy resin and thiol, thereby restoring the mechanical properties of the material. Compared with the prior art, the repair time of the present invention is significantly shortened, and it can maintain a good repair effect under multiple damages and complex environmental conditions.

[0030] In the technical solution of the present invention, the micro-nano carrier adopts SiO2 microspheres with a silanized surface and has a highly controllable pore structure (see attached Figure 1 ), which can effectively load the liquid repair agent. Through vacuum-assisted injection, the liquid repair agent can be fully filled into the pores of the microspheres, making it stable in storage and evenly distributed. At the same time, the nanometer size and high specific surface area of ​​the microspheres ensure that the repair agent is well dispersed inside the material, avoiding local aggregation or sedimentation. In addition, the high reactivity of epoxy and thiol groups is utilized to achieve rapid cross-linking and curing after crack filling. When damage occurs, the liquid repair agent is induced and released by the cracks, filled into the cracks, and reacts rapidly under the influence of environmental conditions (such as humidity or temperature) to form a dense cured layer, restoring the integrity and mechanical properties of the material. The low viscosity of the liquid repair agent enables it to quickly penetrate into the deep layers of the cracks, and the high activity of the cross-linking reaction further shortens the curing time. Compared with traditional repair materials that require external heating or long-term standing, the liquid repair network can complete preliminary repairs in minutes.

[0031] In the present invention, the micro-nano carriers are dispersed in the polyurethane matrix to form a "lattice" structure. Each microsphere is a node for storing and releasing a repair agent. When the crack expands, it will gradually trigger the release of multiple repair agent nodes, forming a synergistic repair effect as a whole. This process is similar to information transmission or signal activation in a network system. Each node in the network structure can work independently, and damage in different areas can independently induce the release of the repair agent.

[0032] The composite material of the present invention can be widely used in various industrial equipment, aerospace vehicles, automobiles, construction, flexible electronic equipment and other fields, and has significant advantages in terms of damage resistance and extended service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1A surface morphology diagram of the micro-nano carrier provided by the present invention;

[0034] Figure 2 These are graphs showing the morphological changes of the composite material provided by the present invention before and after repair, wherein (a) and (c) are macroscopic and microscopic graphs before repair, respectively; and (b) and (d) are macroscopic and microscopic graphs after repair, respectively. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Example 1

[0037] Polyurethane composite material I, including the following components: 50g polyurethane prepolymer, 10g repair agent carrier particles, 15g liquid repair agent, 1g catalyst, 0.5g dispersant, 2g additive (antioxidant)

[0038] The preparation method of the polyurethane composite material I is as follows:

[0039] (1) Disperse SiO2 microspheres (15 g) in anhydrous ethanol to ensure that the particles are fully suspended. Add 0.5 g of γ-aminopropyltriethoxysilane and stir evenly. Reflux at 60°C for 2 h to form a chemical bond between the silane coupling agent and SiO2. Wash with ethanol several times to remove the unreacted coupling agent and dry at 80°C.

[0040] (2) Heat epoxy resin (10 g) to 60°C to make it viscous. Slowly add thiol (3.33 g) and stir evenly. Continue stirring for 10 min to obtain a liquid repair agent. Mix the obtained liquid repair agent with modified SiO2 microspheres at a mass ratio of 1.5:1 and treat under vacuum conditions for 10 min. Ensure that the liquid repair agent penetrates into the pores of the carrier; quickly freeze the carrier injected with the liquid repair agent at -40°C; use freeze drying equipment at -60°C, 10pa vacuum freeze drying for 18 hours to remove excess solvent and ensure stable storage of the repair agent.

[0041] (3) MDI and polyether polyol were reacted at a molar ratio of 1.9:1, a catalyst (1 g) was added, and the mixture was stirred at 200-500 rpm for 2-4 h at 60° C. to obtain the desired polyurethane prepolymer.

[0042] (4) The carrier particles of the encapsulation repair agent are uniformly dispersed in the polyurethane prepolymer, and ultrasonic dispersion is performed for 30 minutes. The prepolymer is formed by a compression molding process, and cured at 50° C. for 4 hours to obtain a polyurethane composite material I.

[0043] Example 2

[0044] Polyurethane composite material II, including the following components: 45g polyurethane prepolymer, 12g repair agent carrier particles, 20g liquid repair agent, 1.5g catalyst, 0.3g dispersant, 1.5g additive (ultraviolet absorber)

[0045] The preparation method and use method of the polyurethane composite material II are the same as those in Example 1 to obtain the polyurethane composite material II.

[0046] Example 3

[0047] Polyurethane composite material III, including the following components: polyurethane prepolymer 55g, repair agent carrier particles 8g, liquid repair agent 12g, catalyst 0.8g, dispersant 0.8g, additive 4g (flame retardant)

[0048] The preparation method and use method of the polyurethane composite material III are the same as those in Example 1, to obtain the polyurethane composite material III.

[0049] Example 4

[0050] Polyurethane composite material IV, including the following components: polyurethane prepolymer 40g, repair agent carrier particles 9g, liquid repair agent 18g, catalyst 1g, dispersant 0.4g, additive 3g (antioxidant)

[0051] The preparation method and use method of the polyurethane composite material IV are the same as those in Example 1, to obtain the polyurethane composite material IV.

[0052] Example 5

[0053] Polyurethane composite material V, including the following components: polyurethane prepolymer 60g, repair agent carrier particles 6g, liquid repair agent 10g, catalyst 1.8g, dispersant 0.6g, additive 1g (ultraviolet absorber)

[0054] The preparation method and use method of the polyurethane composite material V are the same as those in Example 1, to obtain the polyurethane composite material V.

[0055] Example 6

[0056] Polyurethane composite material VI, including the following components: 48g polyurethane prepolymer, 10g repair agent carrier particles, 14g liquid repair agent, 1.2g catalyst, 0.4g dispersant, 2g additive (antioxidant)

[0057] The preparation method and use method of the polyurethane composite material VI are the same as those in Example 1 to obtain the polyurethane composite material VI.

[0058] Example 7

[0059] Polyurethane composite material VII, including the following components: polyurethane prepolymer 55g, repair agent carrier particles 10g, liquid repair agent 12g, catalyst 1g, dispersant 0.5g, additive 3g (flame retardant)

[0060] The preparation method and use method of the polyurethane composite material VII are the same as those in Example 1, to obtain the polyurethane composite material VII.

[0061] Example 8

[0062] Polyurethane composite material VIII, including the following components: polyurethane prepolymer 53g, repair agent carrier particles 7g, liquid repair agent 13g, catalyst 1.5g, dispersant 0.6g, additive 4g (antioxidant)

[0063] The preparation method and use method of the polyurethane composite material VIII are the same as those in Example 1 to obtain the polyurethane composite material VIII.

[0064] Example 9

[0065] Polyurethane composite material IX, including the following components: polyurethane prepolymer 50g, repair agent carrier particles 11g, liquid repair agent 16g, catalyst 1.3g, dispersant 0.5g, additive 3g (flame retardant)

[0066] The preparation method and use method of the polyurethane composite material IX are the same as those in Example 1, to obtain the polyurethane composite material IX.

[0067] Example 10

[0068] Polyurethane composite material X, comprising the following components: 49g polyurethane prepolymer, 9g repair agent carrier particles, 17g liquid repair agent, 1.4g catalyst, 0.6g dispersant, 4g additive (flame retardant)

[0069] The preparation method and use method of the polyurethane composite material X are the same as those in Example 1 to obtain the polyurethane composite material X.

[0070] According to the above-mentioned test method, the performance test of the polyurethane composite material prepared in each embodiment was carried out. The performance test results are shown in Table 1.

[0071] Figure 1The SEM image of the micro-nano carrier is shown. It has a regular porous surface, indicating that its storage capacity of the repair agent is strong. The larger the internal volume, the more repair agent can be encapsulated. The high storage capacity of the repair agent inside the carrier can ensure the material supply during the self-repair process, thereby improving the repair efficiency. And the pore size is uniform, and the release rate of the repair agent can be well controlled, which helps to achieve continuous supply during the repair process and ensure that the crack is completely closed. Figure 2 This is a diagram of the morphological changes of the composite material before and after repair. The repair efficiency is evaluated by artificially creating cracks. From the macroscopic image, it can be seen that the cracks in the material are almost completely repaired after one minute, indicating that the repair efficiency is high. At the same time, the microscopic image further proves that the cracks are not only covered by the surface, but the repair agent also penetrates deep into the cracks, providing effective structural reinforcement.

[0072] From the performance test results, it can be concluded that the self-repairing efficiency of Example 3 is the highest at 96%, and Example 9 has outstanding performance in hardness, impact resistance, tensile strength and self-repairing efficiency, and has the best comprehensive performance.

[0073] Table 1 Coating performance test results

[0074]

[0075]

[0076] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A polyurethane composite material with an embedded liquid repair network, characterized in that: The composition comprises the following raw materials in parts by weight: 40-60 parts of polyurethane prepolymer, 5-20 parts of repair agent carrier particles, 10-30 parts of liquid repair agent and 0.1-1 part of dispersant; The polyurethane prepolymer is prepared by mixing isocyanate and polyol in a molar ratio of 1.8-2.2:1 under the catalysis of a catalyst; The liquid repair agent is prepared by mixing epoxy resin and mercaptan in a mass ratio of 1-4:

1.

2. The polyurethane composite material with an embedded liquid repair network according to claim 1, characterized in that: The repair agent carrier particles are modified SiO2 microspheres.

3. The polyurethane composite material with an embedded liquid repair network according to claim 1, characterized in that: The catalyst is diphenylphosphonic acid, and the dispersant is polyether-modified siloxane.

4. The polyurethane composite material with an embedded liquid repair network according to claim 1, characterized in that: Also includes 0.5-5 parts of additives.

5. The polyurethane composite material with embedded liquid repair network according to claim 4, characterized in that: The additive is a mixture of any one or more of an antioxidant, an ultraviolet absorber and a flame retardant.

6. A method for preparing a polyurethane composite material with an embedded liquid repair network, characterized in that: The following steps are involved: (1) Injection and encapsulation of liquid repair agent: Heat the epoxy resin at 50-60°C to a viscous state; slowly add the thiol under continuous stirring to ensure uniform mixing; continue stirring for 10-15 minutes until a uniform and transparent liquid repair agent is formed; (2) Weighing each raw material according to the weight proportions described in any one of claims 1 to 6, mixing the liquid repair agent with the repair agent carrier particles; treating the repair agent and carrier mixture under vacuum conditions for 10 to 20 minutes to ensure that the liquid repair agent penetrates into the pores of the carrier; rapidly freezing the carrier injected with the liquid repair agent at -40°C; and performing vacuum freeze drying using a freeze drying device to remove excess solvent to ensure stable storage of the repair agent; (3) Preparation of polyurethane prepolymer: preparing a polyurethane prepolymer with controllable viscosity by reacting isocyanate with polyol under the action of a catalyst; (4) Forming of the composite material: The carrier particles of the encapsulated repair agent are ultrasonically dispersed uniformly in the polyurethane prepolymer, and the remaining raw materials are added during the dispersion process. The composite material is then formed by molding, pouring or spraying, and cured at 50-80°C for 2-6 hours to obtain a polyurethane composite material with an embedded liquid repair network.

7. The method for preparing a polyurethane composite material with an embedded liquid repair network according to claim 6, characterized in that: The preparation method of the repair agent carrier particles is as follows: dispersing SiO2 microspheres in anhydrous ethanol to ensure that the particles are fully suspended, adding 0.1-5% of a silane coupling agent, and stirring evenly; refluxing at 60° C. for 2-4 hours to allow the silane coupling agent to form a chemical bond with the SiO2 surface; The unreacted silane coupling agent was removed by washing with ethanol for several times, and then the modified SiO2 microspheres were obtained by drying at 80°C.

8. The method for preparing a polyurethane composite material with an embedded liquid repair network according to claim 7, characterized in that: The silane coupling agent is γ-aminopropyltriethoxysilane or γ-methacryloxypropyltrimethoxysilane.

9. The method for preparing a polyurethane composite material with an embedded liquid repair network according to claim 6, characterized in that: The vacuum pressure in step (2) is 10 Pa, the freeze-drying temperature is -60°C, and the freeze-drying time is 12-24 hours.

Citation Information

Patent Citations

  • Polyurethane / epoxy resin blend with shape memory, self-repairing and recyclability functions and preparation method thereof

    CN110305466A

  • Polyurethane type self-repairing resin

    CN111499833A

  • Self-healing and damage in-situ recognition epoxy resin composite material as well as preparation method and application thereof

    CN115304884A

  • Preparation method of polyurethane composite microcapsule and application of polyurethane composite microcapsule in self-repairing of epoxy resin

    CN118290903A

  • High-temperature-resistant flame-retardant polyurethane foam with self-repairing performance and preparation method thereof

    CN118440388A

Cited By

  • High-strength polyurethane-based road crack repairing material and preparation method thereof

    CN120118507A

  • Para-aramid fiber drainage pipe and preparation method thereof

    CN120735381A

  • Surface conductive type self-repairable airplane discharge brush and preparation method thereof

    CN122534734A